2021
DOI: 10.3390/buildings11120573
|View full text |Cite
|
Sign up to set email alerts
|

Use of Underground Constructions Enhanced with Evaporative Cooling to Improve Indoor Built Environment in Hot Climate

Abstract: Underground constructions (UGCs) have been used globally to accommodate a wide range of building usage, such as offices and shopping malls. Most of these constructions suffer from a lack of natural ventilation as well as daylight, as they are completely built under the surface of the earth. This has caused many issues related to discomfort, impacting the activity and the productivity of users. This study aimed to analyse the effect of the use of UGCs in hot regions, enhanced by partly elevated external walls w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…However, a simulation study on the soil vapour intrusion in a basement shows that it is unpredictable to evaluate, thus the health risks due to poor indoor air quality in a basement requires higher consideration [20]. It was found that the usage of underground construction in hot climates should be encouraged since natural ventilation and daylight can reduce summer temperatures by 3 degrees Celsius and evaporative cooling can cool the indoor environment by roughly 12 degrees Celsius [21]. Although, there is a finding revealed that the connection between energy consumption and U-value of envelopes for underground constructions differs from that for above-ground buildings: enhancing thermal performance of outside walls does not reduce energy consumption and may even increase energy costs [22].…”
Section: Basementmentioning
confidence: 99%
“…However, a simulation study on the soil vapour intrusion in a basement shows that it is unpredictable to evaluate, thus the health risks due to poor indoor air quality in a basement requires higher consideration [20]. It was found that the usage of underground construction in hot climates should be encouraged since natural ventilation and daylight can reduce summer temperatures by 3 degrees Celsius and evaporative cooling can cool the indoor environment by roughly 12 degrees Celsius [21]. Although, there is a finding revealed that the connection between energy consumption and U-value of envelopes for underground constructions differs from that for above-ground buildings: enhancing thermal performance of outside walls does not reduce energy consumption and may even increase energy costs [22].…”
Section: Basementmentioning
confidence: 99%
“…Among these four aspects, TC and IAQ are commonly suggested for priority consideration to avoid healthrelated symptoms, absenteeism, and loss of concentration [10,11]. Thus, to guarantee the health and efficiency of occupants, a better indoor environment with suitable TC and IAQ is suggested [12], and many studies have focused on particular methods to achieve better IEQ, such as the use of windcatchers [13][14][15].…”
Section: Introductionmentioning
confidence: 99%